Designing Educational Newsletter Interventions: An Example That Supported Grandfamilies’ Physical Wellness Needs - Priscilla Brenes; Mary Meck Higgins ([TEST] Journal of Extension, 2021)
Effective newsletters have theory-based content and designs tailored to their readers and offer limited-cost community-level approaches to providing helpful, relevant, and engaging information. In accordance with this, we offer an example of a newsletter intervention that supported grandfamilies’ physical wellness needs. Six issues of a brief mail-delivered newsletter were sent yearly for up to 5 years to low-income custodial grandparents. In evaluating the newsletter, most respondents reported reading it, discussing its information, and having greater awareness, knowledge, and motivation or confidence regarding wellness recommendations. Furthermore, 91% described improving 1 or more of their grandfamilies’ cooking, eating, or physical activity practices.
Keywords: mailed newsletter; intervention; health and wellness education; grandparents raising grandchildren; Supplemental Nutrition Assistance Program (SNAP)